Way of Life of Hmong Ethnic Group :: The case study of Ban Mae Sa Mai, Pongyang Sub-district, Maerim District, Chiangmai Province - Jingjing, Gao; Onkam, Imthira (Academic and Research Journal of Liberal Arts (Online), 2021)
This article aims to study the way of life of Hmong ethnic group in Ban Mae Sa Mai, Pongyang Sub-district, Maerim District, Chiangmai Province. This Research is a qualitative research that studies data from documentation and in the field by using both participatory observations, non-participatory observations and in-depth interviews by interviewing the sample group or until the data is saturated and meets the research’s objective. The research finds that the way of life of Hmong ethnic group at Ban Mae Sa Mai consists of three aspects: 1) Lifestyle, this group of people continuously practice their the traditional way of life 2) Culture, the art on fabric of their costume, which represent their beliefs, rituals and wisdom that they maintain and inherit strictly from their ancestors. 3) Tradition, the people practice their traditional way of life and social traditions according to their own process. In addition, they inherit their own way of life through important elements such as family members, community cooperation and support from government and associations. Consequently, they remain distinct on their own identity. However; despite the rapid change and development of the society, Hmong ethnic group is able to maintain and inherit their own way of life until the present day.